Disturbance observer-based feedback linearization control of an unmanned quadrotor helicopter. (October 2016) - Aboudonia, Ahmed; El-Badawy, Ayman; Rashad, Ramy
Feedback linearization is widely used for the purpose of quadrotor control. Unfortunately, feedback linearization is highly sensitive to any quadrotor model uncertainties. This paper provides feedback linearization-based control with robustness by integrating it with a disturbance observer. The proposed approach maintains the simplicity of the control structure without ignoring the high nonlinearities existing in the model by considering these nonlinearities as disturbances to be attenuated by the disturbance observer. Thus, the requirement to include complex high-order Lie derivatives in the controller is eliminated even in the presence of the high nonlinearities. Simulation results show that the proposed controller successfully force the quadrotor to follow the desired position and heading trajectories in the presence of different types of disturbances including ignored nonlinear dynamics, wind disturbances and partial actuator failure.